Human resource training at VTC Digital Company - Tran, Ngoc Anh (Khoa Quốc tế, ĐHQGHN, 2020)
Based on actual requirement, theoretical basis, documents, preceding studies on the issue about human resource management in general and human resource training in particular, I have chosen topic for my thesis: “Human resource training at VTC company”. In this thesis, I use secondary data sources from the documents, reports of the Human Resource Department and reports from other departments of the company and primary data sources from surveys with employees and interviews with the Director, Vice Directors and head managers of departments to analyze the situation of employee training at the company.